Analisis Faktor Kendala dalam PengajuanSertifikat Halal. (Studi Kasus: Pelaku Usaha Mikro, Kecil dan Menengah Makanan Beku diJabodetabek) - Maryati, T.; Syarief, R.; Hasbullah, R. (Jurnal Ilmu Produksi dan Teknologi Hasil Peternakan, 2016)
Indonesia with high Muslim community is potential market for halal products. High percentage of Small Medium Enterprises make it as driver of commerce in Indonesia, but the fact those enterprises cannot submit halal certificate makes this research conducted to identify enterprises characteristic, analyze the constraints and formulate strategies in halal certificate submission. Information extracted from 30 frozen food enterprises in Jakarta, Bogor, Depok, Tangerang dan Bekasi and 10 experts in the field related with convenience and purposive sampling are enterprises educational background, business period, earnings, and industrial facilities including the machines used, how many are unlicensed industrial, marketing authorization, and halal certificate. The determination of alternative uses analytical hierarchy process with the help of Expert Choice 2003. Results showed that enterprises are micros that do not have proper production facility and using simple technology. Marketing authorizationis obstacle in halal certificates submission. Improving the competitiveness (0.575) with assistance (0.321) from Badan Pengawas Obat dan Makanan (0.484) is the main priority. Factors the most influenceare production facility (0.572), raw material (0.233), attitude of enterprises (0.838) and legality (0.432). The best alternative strategies recommended are fostering Good Production (0.343), Bureaucratic of marketing authorization accelerated and simplified (0.169) and intense coaching (0.153).